Obtaining Gossypol Acetic Acid (Gsk) From Gossypol - Kurbanova A.Dj; Islamov A.Kh; Komilov K.U; Ibragimov A.S. (Peerian Journals Publishing, 2023)
This article provides information on the biological properties of cotton and the extraction of Gossypol acetic acid (GSK) from technical Gossypol
Keywords: Gossipium; technical Gossypol; Bactericide